PENGARUH SEKTOR PARIWISATA TERHADAP PENDAPATAN ASLI DAERAH DI EKS KARESIDENAN MADIUN - Elnin Efrintya; Muchtolifah Muchtolifah; Sishadiyati Sishadiyati (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2021)
Abstract Tourism is one of the sector that can increase regional income in the service industry. The purpose of this study was to determine the effect of the number of hotels, tourist attractions, and tourist visits on local revenue in the Madiun Residency. This study uses panel data with time series data for the 2015-2019 period and with cross-sectional data for six districts/cities obtained from the BPS website for each district. The type of survey is a quantitative survey using panel data regression analysis processed with the Eviews 10 tool. The results show that simultaneously it is found the number of hotels, the number of tourist destinations, and the number of tourist visits have a significant effect on the local economy with a value of sig 0.0000078 <0.05. Partially, the results show that the number of hotels has a significant effect on local revenue with a value of 0.0056 <0.05 and the number of tourist visits has no significant effect on income native to the area with value 0.2741 > 0.05.